CITY BRANDING DI JEMBER : ANALISIS PERSPEKTIF DARI PENGUNJUNG - Ardian Jaya Prasetya; Yunanto Tri Laksono; Candraningrat Candraningrat (UNUSA Press, 2021)
This study aims to analyze the effect of brand attitude and brand image on brand preference through mediating brand equity. The data collection technique used was a survey through a questionnaire given to respondents. The population determined in this study is people who have visited the City of Jember. The samples taken in this study were 130 people. The data analysis technique used is Partial Least Square (PLS) using SmartPLS 2.0 software. This study provides several results, among others: 1) The attitude of influencing the brand does not have a significant positive effect on brand preference; 2) Brand image has a significant positive effect on brand preference; 3) The attitude of influencing the brand has a significant positive effect on brand equity; 4) Brand image has a significant positive effect on brand equity; 5) Brand equity has no significant positive effect on brand preference; 6) The attitude of influencing the brand indirectly has no significant positive effect on brand preference through brand equity; 7) Brand image indirectly has a significant positive effect on brand preference through brand equity.